2023
DOI: 10.3389/fmicb.2023.1192035
|View full text |Cite
|
Sign up to set email alerts
|

Total yeast and mold levels in high THC-containing cannabis (Cannabis sativa L.) inflorescences are influenced by genotype, environment, and pre-and post-harvest handling practices

Zamir K. Punja,
Li Ni,
Samantha Lung
et al.

Abstract: Total yeast and mold (TYM) levels in inflorescences of high THC-containing Cannabis sativa (cannabis) are regulated to ensure that medicinal and recreational users, especially those with immunocompromised systems, are not exposed to potentially harmful levels. In North America, the limits imposed range from 1,000–10,000 cfu/g of dried product to 50,000–100,000 cfu/g, depending on the jurisdiction. Factors affecting a build-up of TYM in cannabis inflorescences have not been previously researched. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…Early detection of disease symptoms in stock plants is important to prevent pathogens from spreading within the growing environment. There are several diagnostic approaches that have been described to detect cannabis pathogens, and a number of commercial laboratories provide testing services for a range of pathogens [4,7,19,26]. The practice of culling and replenishing stock plants is a standard component of IDM programs when diseased plants are detected [31].…”
Section: Testing For Pathogen Presence and Eradicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Early detection of disease symptoms in stock plants is important to prevent pathogens from spreading within the growing environment. There are several diagnostic approaches that have been described to detect cannabis pathogens, and a number of commercial laboratories provide testing services for a range of pathogens [4,7,19,26]. The practice of culling and replenishing stock plants is a standard component of IDM programs when diseased plants are detected [31].…”
Section: Testing For Pathogen Presence and Eradicationmentioning
confidence: 99%
“…Various factors influence the levels of yeast and mold contamination, which are discussed in the following sections. Testing for the presence of yeasts and molds on cannabis inflorescences prior to harvest is not routinely performed, although research studies have shown that this can provide useful information on the population levels and species that may be present [19]. These populations are influenced by many factors, including the genotype of cannabis being grown, the environmental conditions prior to harvest, particu-larly temperature and relative humidity, the presence of excessive leaf litter, and the time of year [19].…”
Section: Flowering Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Early detection of disease symptoms in stock plants is important to prevent pathogens from spreading within the growing environment. There are several diagnostic approaches that have been described to detect cannabis pathogens, and a number of commercial laboratories provide testing services for a range of pathogens [ 4 , 7 , 19 , 26 ]. The practice of culling and replenishing stock plants is a standard component of IDM programs when diseased plants are detected [ 31 ].…”
Section: Cannabis Pathogens: Symptoms and Management Approaches At Di...mentioning
confidence: 99%
“…The prevalent pathogens affecting cannabis crops in greenhouses have been recently characterized and described [ 7 ], providing diagnostic information that is required for IDM implementation. Accurate diagnosis of the pathogen(s) involved in a disease syndrome is an important component of IDM, and several diagnostic methods have been described [ 4 , 7 , 16 , 17 , 18 , 19 ]. In this review article, we describe the most important pathogens of cannabis crops cultivated under greenhouse conditions and highlight the various growth stages at which IDM approaches can be implemented during the crop production cycle, which generally occurs over 12–15 weeks ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%